2004
DOI: 10.1037/0735-7044.118.4.805
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Inhibits Maternal Aggression in Mice.

Abstract: Lactating females that fiercely protect offspring exhibit decreased fear and anxiety. The authors tested whether decreased corticotropin-releasing factor (CRF), an activator of fear and anxiety, plays a functional role in maternal aggression. Intracerebroventricular (icv) injections of CRF (1.0 and 0.2 microg, but not 0.02 microg) significantly inhibited maternal aggression but not other maternal behaviors. The CRF antagonist D-Phe-CRF(12-41) had no effect. Maternal aggression and icv CRF (0.2 microg) induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
177
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(184 citation statements)
references
References 47 publications
6
177
1
Order By: Relevance
“…Previous studies have found that isoflurane can depress c-Fos in the spinal cord (Jinks et al, 2002), but elevate it in the hypothalamus in aged rats (Jansson et al, 2004), so it is not clear how isoflurane may have acted in this study, if at all on c-Fos expression. As indicated above, the use of isoflurane in association with injection here was aimed to reduce stress effects of injection and its previous use in association with injection has not been found not to overtly impair aggression or other maternal behaviors (D'Anna et al, 2005;D'Anna and Gammie, 2006;Gammie et al, 2004). Exactly whether or how CDP and isoflurane may interact at the doses used in this study would need to be examined in subsequent experiments.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have found that isoflurane can depress c-Fos in the spinal cord (Jinks et al, 2002), but elevate it in the hypothalamus in aged rats (Jansson et al, 2004), so it is not clear how isoflurane may have acted in this study, if at all on c-Fos expression. As indicated above, the use of isoflurane in association with injection here was aimed to reduce stress effects of injection and its previous use in association with injection has not been found not to overtly impair aggression or other maternal behaviors (D'Anna et al, 2005;D'Anna and Gammie, 2006;Gammie et al, 2004). Exactly whether or how CDP and isoflurane may interact at the doses used in this study would need to be examined in subsequent experiments.…”
Section: Discussionmentioning
confidence: 97%
“…LS is a prime candidate for modulation of maternal defense by BDZs because it is associated with fear and anxiety (Numan and Insel, 2003;Pesold and Treit, 1996;Singewald et al, 2003) and previously has been hypothesized to be a critical site of negative regulation for maternal aggression (D'Anna et al, 2005;Gammie et al, 2004). For example, for three peptides that inhibit maternal aggression, CRF (Gammie et al, 2004), urocotin (Ucn) 1, and Ucn 3 (D' Anna et al, 2005), c-Fos activity in LS was elevated with treatment at the dose that impaired aggression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations